Embedding Computational Thinking into Authentic Technology Practice (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, 2023)
This paper presents the findings from a pilot study aimed to investigate how the computational thinking aspect of digital technologies can be embedded authentically into students’ technological practice. The project explored teaching and learning computational thinking in context and particularly focus on technological needs and practice for young Māori learners.There is recognition internationally about the need for digital technologies within the curriculum. Computational thinking is a critical component of this and is defined as an approach to problem-solving, designing computer systems, and understanding related human behaviours, while drawing on fundamental ideas of computing. Therefore, it is critical that all students acquire computational thinking skills. Technology practice is most successful when embedded within authentic contexts, thus this paper presents a study that facilitated the learning of two concepts of computational thinking: sequencing and orientation within culturally embedded technology practice. The study’s vision is to assist mainstream Māori learners from low socio-economic backgrounds to develop an understanding of related concepts of computational thinking. The research design drew on Māori values and practice that situates learning within authentic Māori contexts. Kaupapa Māori pedagogies were used in our design-based intervention programme to achieve the research goal. The focus of the project was to improve digital technologies learning outcomes to ensure Māori tamariki (children) see themselves as comfortably situated in a digital world.